Analysis of Outpatient Repeat Visit Interest using the Marketing Mix Method: Literature Review - Loveni Parenti, Uyun; Prayoga, Diansanto (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Hospitals must provide safe, high-quality, and effective health services in accordance with standards, focusing on patient satisfaction and the implementation of appropriate marketing strategies. Through marketing mix analysis, this study aims to analyze the interest in patients' return visits to outpatient services. The objective of this research is to examine whether this marketing mix method can stimulate interest in the return visits of outpatient patients in healthcare services. The method used is a literature review. The results indicate that the